Generiranje LALR tabel - Kokol, Peter (Informatica (Ljubljana), 1984)
Algorithms and procedures for LALR(1) tables generator are given. To procedure the LALR(1) tables for some language we must input the grammar of this language in BNF meta language. The described generator was tested for different languages. A short example is given at the end of this paper.
Keywords: algorithms; generiranje LALR tabel; implementacija jezika; LALR tabele; LALR tables; LALR tables generator; LR razpoznavalniki